The impact of an 8-year mass drug administration programme on prevalence, intensity and co-infections of soil-transmitted helminthiases in Burundi. Issue 1 (December 2016) - Ortu, Giuseppina; Assoum, Mohamad; Wittmann, Udo; Knowles, Sarah; Clements, Michelle; Ndayishimiye, Onésime; Basáñez, Maria-Gloria; Lau, Colleen; Clements, Archie; Fenwick, Alan; Magalhaes, Ricardo
Abstract Background Soil-transmitted helminth (STH) infections are amongst the most prevalent infections in the world. Mass drug administration (MDA) programmes have become the most commonly used national interventions for endemic countries to achieve elimination. This paper aims to describe the effect of an 8-year MDA programme on the prevalence, intensity of infection and co-infection of STH in Burundi from 2007 to 2014 and critically appraise the trajectory towards STH elimination in the country. Results Annual STH parasitological surveys (specifically, a "pilot study" from 2007 to 2011, an "extension study" from 2008 to 2011, and a "national reassessment" in 2014;n  = 27, 658 children), showed a significant drop in prevalence of infection with any STH ("pooled STH") between baseline and 2011 in both studies, falling from 32 to 16 % in the pilot study, and from 35 to 16 % in the extension study. Most STH infections were of low intensity according to WHO classification. The national reassessment in 2014 showed that prevalence of pooled STH remained significantly below the prevalence in 2007 in both studies but there was no further decrease in STH prevalence from 2011 levels during this time. Spatial dependence analysis showed that prevalence ofTrichuris trichiura andAscaris lumbricoides had a tendency to cluster over the years, whilst only trends in spatial dependence were evident for hookworm infections. Spatial dependence fluctuated over the course of the programme forAscaris lumbricoides andTrichuris trichiura. However, spatial trends in spatial dependence were evident in 2010 forAscaris lumbricoides . Analysis of spatial clustering of intensity of infection and heavy infections revealed that the intensity changed over time for all parasites. Heavy intensity was only evident inAscaris lumbricoides for 2008 and did not appear in proceeding years and other parasites. Conclusions These results demonstrate that sustained annual MDA significantly reduced the prevalence of STH infection in school-age children but was unable to achieve elimination. Additionally, significant decline in prevalence was accompanied by a drop in spatial clustering of infection indicators across all sites from 2008. The lack of consistency in the results of the spatial dependence analysis highlights that MDA programmes can interrupt the normal transmission dynamics of STH parasites.